Percutaneous Transvenous Mitral Commissurotomy in 71 Years Old Woman with Mitral Stenosis- A Case Report - Majumder, AAS; Hasnat, Mohammad Abul; Islam, AKMM; Ullah, M; Rahman, MZ; Zaman, S; Rahman, MM; Alamgir, MH (Cardiovascular Journal, 2013)
Cardiovascular Journal Volume 6, No. 1, 2013, Page 68-70 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16119